Uso de biomassa de algas para a peletização de sementes e desenvolvimento de plântulas de Bowdichia virgilioides Kunth - Montanhim, Graziela Cristina (2013)
Algae are organisms with which studies have been made on the uptake of carbon dioxide, as a source of lipids for research on biofuels such as fertilizers and soil. But little is known about the interaction of such organisms with higher plants. Thus, the general objective of this master thesis was to reuse the algal biomass of Selenastrum capricornutum Printz (Chlorophyceae class) e Chlorella sorokiniana Shihira e Krauss (Trebouxiophyceae class) in pelleting seed Bowdichia virgilioides, native to the Brazilian Savanna that are classified as threatened with extinction and whose wood has attributes for the furniture industry, besides the medicinal properties already reported in other studies. First, the seeds were grown in a greenhouse, with the following treatments: a) seeds naked; b) pelleted seeds with white glue based on polyvinyl acetate diluted to 8% at water and gypsum; c) seeds pelleted with glue based white polyvinyl acetate diluted to 8% at wet algal biomass of Selenastrum capricornutum and gypsum; d) pelleted seeds with white glue based polyvinyl acetate diluted to 8% at wet algal biomass of Chlorella sorokiniana and gypsum. Fungicide and insecticide were added to the silicato and gypsum for agricultural according to industry directions. The parameters mean emergence time (days), weight (g) dry and cool, length (cm) of aerial and root portions and number of nitrogen fixing nodules in the roots don t showed statistically significant difference between treatments. The variable "emergency percentage" showed that pelleted seeds with C. sorokiniana biomass as a cement material constituent showed value equivalent to conventional treatment (naked), paving the way for new studies pelleting with agal biomass of that species. As higher be the algae intracellular biochemical values, higher be the chances to achieve satisfactory results, because the seed can be use algae biochemical components at its development. In a second stage, there was pelleted seed sown in an area of brazilian savanna and the treatments were: a) naked seed; b) pelleted seeds with white glue based on polyvinyl acetate diluted to 8% at water and gypsum; c) pelleted seeds with white glue based on polyvinyl acetate diluted to 8% at wet algal biomass of Selenastrum capricornutum and gypsum with fungicide and insecticide; d) pelleted seeds with white glue based on polyvinyl acetate diluted to 8% at water and silicate for agricultural; and e) pelleted seeds with white glue based on polyvinyl acetate diluted to 8% at wet algal biomass of Selenastrum capricornutum and silicate for agricultural. Fungicide and insecticide were added to the silicato and gypsum for agricultural according to industry directions. For this experiment hood, it was observed that treatment with only gypsum had a significantly lower percentage of emergence. The treatment with silicate was considered as an effective material coating to the sucupira seed pelleting process, cultivating in savanna field. Thus, the alga Chlorella sorokiniana showed to be an efficient cementing material for pelleting process and silicate for agricultural a promising coating material, when it comes to planting in the field.